HUBUNGAN PIJAT BAYI DENGAN KUALITAS TIDUR BAYI - Zurhayati Zurhayati; Nurul Hidayah; Desmariyenti Desmariyenti (Ensiklopedia of Journal, 2022)
In Indonesia, around 44.2% of babies have problems sleeping, but 72% of parents do not consider it a problem. And if it is considered a problem, they consider it a minor problem, while the baby's growth disorders can be caused by sleep problems, but it also affects immune function and disrupts the endocrine system. This study aims to see the relationship between baby massage and infant sleep quality in the PMB Afiyah Pekanbaru Working Area in 2021. Quantitative research, correlation analysis, samples were taken by purposive sampling totaling 23 infants. Checklist sheet as an instrument in research. Data analysis using univariate and bivariate analysis. The results of the Chi-Square Test show p-value = 0.000 and the degree of error = 0.05, which means that there is a relationship between baby massage and baby sleep quality in the PMB Afiyah Pekanbaru Working Area in 2021. Suggestions, it is hoped that this research can be used as an idea or comparison for research The next one is still discussing baby massage.Keywords: Baby Massage, Sleep Quality, Baby